Smoking and its effects on heart rate variability - Taan Al. Awar, Dina H.; Al Yafei, Amani H.; Al Fehaidi, Al Anoud S. (International Journal of Research in Medical Sciences, 2022)
Due to smoking's widespread prevalence, it is necessary to explore cost-effective and practical prognostic markers indicating its health effects. Heart rate variability (HRV) may be used to foresee the long-term repercussions of smoking as a simple and affordable approach of forecasting cardiovascular health complications. Smoking has been proven to have a detrimental effect on HRV, which may have a detrimental effect on cardiovascular health. Additionally, we present an overview of the different HRV measurements and their diagnostic utility in the context of heart failure. There is a very detailed look at all the available data on how smoking affects HRV, as well as how different HRV indices show changes in the activity of the body's autonomic nervous system when people smoke. Smoking has been shown to change the autonomic nervous system's normal function, including an increase in sympathetic drive, a decrease in HRV, and a decrease in parasympathetic control. The possible reasons for this decrease in HRV and how it might affect patients are thoroughly discussed.